Answering Multidimensional Challenges Through the Implementation of the 2013 Curriculum: Characteristics of Character Education - Syahidi, Khaerus; Muhammad Sarjan; Joni Rokhmat; Syahrial A; I Gde Mertha; Kurniawan Arizona; Syamsuddin; Ramdhani Sucilestari (Yayasan Arfah Bin Haji Muhammad Saleh, 2025)
The implementation of character education in formal education environments has an effective influence in overcoming the phenomena of anarchism, imposition of will, student fights, proliferation of drug dealers and users, environmental crises, moral crises, and various other social tendencies. Formal education is an organized, directed, and measurable education system. The 2013 Curriculum orients and emphasizes the Strengthening of moral, affective, and conceptual values ​​​​of KI-1 (spiritual attitudes), KI-2 (social attitudes), KI-3 (knowledge), and KI-4 (application of knowledge). The implementation of character education in the 2013 Curriculum can be developed by integrating cognitive, affective, and psychomotor aspects. In addition, to encourage and facilitate the realization of Synergy between formal, non-formal and informal education, and encourage to Continue to improve the competence and role models of educators to implement the 2013 Curriculum